Murabahah Default Dispute From the Perspective of Maqashid Syariah (Case Study Decision No. 01/Pdt.G.S/2021/PA. Kph) - Isman Isman; Atania Saida El Rosyidah (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
The verdict of the Kepahiang Religious Court, Case Number 01/Pdt.G.S/2021/PA.Kph, reflects a tension between the formalistic application of positive law and the values of maqāṣid al-sharīʿah, which emphasize justice and preventive benefit in resolving Islamic economic disputes. This study aims to analyze the legal considerations and the construction of maqāṣid al-sharīʿah in a murābaḥah contract default case by examining the consistency between the judge’s legal reasoning and the principles of maqāṣid al-sharīʿah, namely ḥifẓ al-māl (protection of wealth), ḥifẓ al-‘aqd (protection of contract), and ḥifẓ al-‘adl (protection of justice). Employing a normative-juridical method with a case-conceptual approach and content analysis of the Compilation of Sharia Economic Law (KHES), the Indonesian Civil Code (KUHPerdata), and DSN-MUI Fatwas, the study finds that the judge adopted systematic and grammatical interpretation through legal logic techniques such as subsumption, exclusion, derogation, and non-contradiction. However, the ruling remains curative and mechanistic in nature, as it primarily focuses on punitive measures for contractual breach. These findings reveal an epistemic disparity between the formal rationality of positive law and the preventive, benefit-oriented rationality of sharīʿah. This research contributes by proposing a maqāṣidic legal reasoning framework as an integrative paradigm to reconcile the rationality of positive law with the ethical rationality of maqāṣid al-sharīʿah in the practice of Islamic economic adjudication in Indonesia.